Minimum Marriage Age: Study of Fiqh of Four Madhabs - Maisarah; Afrizal; Zulfahmi; Fizal Mauliza; Faisal Murni (Britain International for Academic Research (BIAR) Publisher, 2019)
Fiqh of four madhab (Hanafi, Maliki, Shafi'i and Hambali) permit the marriage of minors, so that parents tend to marry their children at an underage. This ppinion is criticized in modern times who want a minimum age of marriage. The question arises how the interpretation of the four madhab (Islamic jurisprudence) of thought is used and are there other arguments that can be used in reinterpreting the existence of a minimum age of marriage. This study uses some methods, firstly, to examine the verses and hadith to find out whether there are cues about the minimum age of marriage or not. Secondly, to reinterpret using the ta‘liliyyah method and the termiyyah of the arguments used by the religious and contemporary scholars. The result shows that the madhab declares Surah al-Thalaq as the proposition regarding the ability of marriages of young children. According to the author, the logic is incorrect because there is no need to iddah for virgin women contained in Surah al-Ahzhab verse 49; The religious scholars also use it as the proposition of the Prophet's marriage hadith. with ‘Aisha r.a when she was a child, even though this incident occurred in Mecca before the Muslim period and before the hadith about the guardian's obligation to ask permission for a girl or widow. This study also finds other verses that can be used as arguments in limiting the age of marriage, namely Surat al-Nisa 'verses 5-6 and 9, the hadith of Ibn Mas'ud and maslahah to be achieved from a marriage, which explicitly states that both adult and maturity both physically and mentally as a condition of marriage.